Nellie's promise - Tripp, Valerie, 1951- (Pleasant Company Publications, 2004)
After being orphaned, Nellie and her two younger sisters find hope when Samantha's family in New York City wants to adopt the girls, but when Uncle Mike shows up and threatens to ruin it all, Nellie must find a way to keep her promise to her dying mother without losing her new family.